2007
DOI: 10.5194/acp-7-1275-2007
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ground-based observations of O<sub>3</sub>, HCl, N<sub>2</sub>O, and CH<sub>4</sub> over Toronto, Canada by three Fourier transform spectrometers with different resolutions

Abstract: Abstract. An intercomparison of three Fourier transform spectrometers (FTSs) with significantly different resolutions is presented. The highest-resolution instrument has a maximum optical path difference of 250 cm, and the two lowerresolution instruments have maximum optical path differences of 50 cm and 25 cm. The results indicate that the two lower-resolution instruments can retrieve total column amounts of O 3 , HCl, N 2 O and CH 4 using the SFIT2 retrieval code with percent differences from the high-resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
6
25
0
Order By: Relevance
“…These differences are comparable in magnitude with other side-byside instrument comparisons carried out at Eureka (Fu et al, 2008;Paton-Walsh et al, 2009;Batchelor et al, 2009) and around the globe (Goldman et al, 1999;Griffiths et al, 2005;Wunch et al, 2007).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These differences are comparable in magnitude with other side-byside instrument comparisons carried out at Eureka (Fu et al, 2008;Paton-Walsh et al, 2009;Batchelor et al, 2009) and around the globe (Goldman et al, 1999;Griffiths et al, 2005;Wunch et al, 2007).…”
Section: Resultssupporting
confidence: 84%
“…The only difference from that work is that for PARIS-IR, retrievals have been performed on a 29-rather than the 38-layer grid used for the DA8 and 125HR, to allow for its lower spectral resolution. This has been previously shown to result in differences in the retrieved column of less than 0.6% (Wunch et al, 2007), but helps to reduce unphysical oscillations in the retrieved profile. A priori VMR profiles and covariances, described in Sung et al (2010), were consistent for all three instruments, while ad hoc SNR ratios, which are used for determining the measurement covariance, were selected for each gas for each instrument using the trade-off curve method described in Batchelor et al (2009) to customize for the noise level in the spectra of the individual instruments.…”
Section: Ground-based Ftir Spectrometersmentioning
confidence: 96%
“…Comparisons of these data sets are underway (Kerzenmacher et al, 2005;Sung et al, 2007). PARIS-IR and the U of T FTS also took part in an intercomparison study at the Toronto Atmospheric Observatory in August 2005 which is described by Wunch et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…For the apodization function, the DA8 FTS used a Hamming function and PARIS-IR used a boxcar function. In earlier comparisons, it was demonstrated that it is necessary to have a well-characterized instrument line shape (ILS) in order to retrieve accurate total columns of stratospheric gases from PARIS-IR spectra (Wunch et al, 2007). In this current work, we used the LINEFIT program (Hase et al, 1999, version 11) to retrieve ILS information for the two FTSs from N 2 O features between 2400 and 2800 cm −1 .…”
Section: Spectral Analysis and Retrievals For Ground-based Ftssmentioning
confidence: 99%